2017
DOI: 10.1136/bmjopen-2017-016317
|View full text |Cite
|
Sign up to set email alerts
|

Assessing oral medication adherence among patients with type 2 diabetes mellitus treated with polytherapy in a developed Asian community: a cross-sectional study

Abstract: ObjectivesThe disease burden of type 2 diabetes mellitus (T2DM) is rising due to suboptimal glycaemic control leading to vascular complications. Medication adherence (MA) directly influences glycaemic control and clinical consequences. This study aimed to assess the MA of patients with T2DM and identify associated factors.DesignAnalysis of data from a cross-sectional survey and electronic medical records.SettingPrimary care outpatient clinic in Singapore.ParticipantsAdult patients with T2DM.Main outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 32 publications
9
89
3
7
Order By: Relevance
“…The presence of diabetes complications or comorbidities was not associated with medication adherence. This is in line with results obtained in a study in Singapore . Patients who did not have medical insurance or enough money were also less adherent treatment, highlighting the need for better social security programmes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The presence of diabetes complications or comorbidities was not associated with medication adherence. This is in line with results obtained in a study in Singapore . Patients who did not have medical insurance or enough money were also less adherent treatment, highlighting the need for better social security programmes.…”
Section: Discussionsupporting
confidence: 88%
“…Longer working hours was associated with decreased adherence since these patients may have difficulty attending to treatment, similar to a study done in Singapore . No relationship between cigarette smoking or alcohol consumption and medication adherence was found.…”
Section: Discussionsupporting
confidence: 77%
“…Participants responded to five items (e.g., I forget to take my medicines) on a 5-point scale from "always" to "never," and a total score of 25 and more indicated better adherence to medications [38]. The MARS has been previously used for patients with T2DM in Singapore [39]. In this study, Cronbach's alpha was 0.6967.…”
Section: Methodsmentioning
confidence: 84%
“…32 In studies elsewhere, similar and lower non-adherence rates have been found, also using the MARS questionnaire. 26,33 Therefore, a minimum sample size of 180 patients per therapeutic drug group was required based on the formula for prediction models with a binary outcome, 34 when including maximum of 9 possible independent variables in the multivariate analysis and assuming a proportion of non-adherence of 50%. With an expected distribution of 2:1 between patients receiving antihypertensive drugs and antihyperlipidemic drugs, 540 patients need to be recruited in the most conservative scenario of no overlap in the use of both therapeutic groups.…”
Section: Sample Size Calculationmentioning
confidence: 99%